Hepatitis C virus NS5A protein enhances gluconeogenesis through upregulation of Akt‐/JNK‐PEPCK signalling pathways. (4th December 2013) - Kuo, Yi‐Chen; Chen, I‐Yin; Chang, Shin C.; Wu, Shun‐Chi; Hung, Tzu‐Min; Lee, Po‐Huang; Shimotohno, Kunitada; Chang, Ming‐Fu
Abstract Background & Aims Hepatitis C virus (HCV) infection is highly associated with the type 2 diabetes mellitus, but the detailed mechanisms by which the viral proteins are involved in the clinical outcome remain unclear. Methods A cDNA microarray analysis was performed following introducing an NS5A‐encoding plasmid or a control vector into a mouse system by hydrodynamics‐based transfection. Differentially expressed genes that are associated with gluconeogenesis were selected and their expression levels in HCV patients, in NS5A‐expressing systems, and in the viral subgenomic replicon system were further examined by real‐time quantitative polymerase chain reaction and Western blot analysis. Results Differential gene expression including an upregulation of the gluconeogenic rate‐limiting enzyme phosphoenolpyruvate carboxykinase (PEPCK) compared with controls was detected in mouse hepatocytes expressing HCV NS5A and in HCV patients with diabetes. In addition, an NS5A‐dependent increase in glucose production was demonstrated in human primary hepatocytes. The upregulation of PEPCK and peroxisome proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α) were also detected in NS5A‐expressing cells and in the viral genotype 1b subgenomic replicon system. Further studies demonstrated that the NS5A‐mediated upregulation of PEPCK and PGC‐1α genes were resulted from the activation of PI3K‐Akt and JNK signalling pathways. In addition, the expression levels of the forkhead transcription factor FoxO1 and the liver‐enriched transcription factor HNF‐4α were increased in HCV NS5A‐expressing cells. Conclusions By upregulating the expression of PEPCK gene via its transactivators FoxO1 and HNF‐4α, and the coactivator PGC‐1α, the NS5A promotes the production of hepatic glucose which may contribute to the development of HCV‐associated type 2 diabetes mellitus.